Transcultural Nursing Competency among Professional Nurses in Bangkok Hospital, Eastern Region - Apichaijaroen, Naratree; Khumyu, Areerut; Deoisres, Wannee (Journal of Phrapokklao Nursing College, Chanthaburi, 2020)
This descriptive comparative research aimed to describe the transcultural nursing competency and to compare the transcultural nursing competency in terms of work experience and attitude toward taking care of culturally diverse clients among professional nurses. The samples consisted of 292 professional nurses working in Bangkok Hospitals, eastern region. The research instruments included the demographic questionnaire, the attitude toward taking care of culturally diverse clients questionnaire with the reliability of .92, and the transcultural nursing competency assessment form with the reliability of .92. Data were collected from March to April, 2018. Statistics used for data analysis included frequency, percentage, mean, standard deviation, one-way ANOVA, and independent t-test. The research results revealed that 1) the overall mean score of transcultural nursing competency of professional nurses was at a high level (M = 3.61, SD = .40); 2) professional nurses with different work experiences had no different mean scores of transcultural nursing competency; and 3) professional nurses with different attitudes toward taking care of culturally diverse clients had statistically significant different mean scores of transcultural nursing competency (t = 13.584, p < .001). This research suggests that nursing administrators should promote transcultural nursing competency as well as enhance attitude toward taking care of culturally diverse clients among professional nurses.